Exploration of genetically encoded voltage indicators based on a chimeric voltage sensing domain - Mishina, Yukiko; Mutoh, Hiroki; Song, Chenchen; Knöpfel, Thomas (Frontiers in Molecular Neuroscience, 2014)
Deciphering how the brain generates cognitive function from patterns of electrical signals is one of the ultimate challenges in neuroscience. To this end, it would be highly desirable to monitor the activities of very large numbers of neurons while an animal engages in complex behaviours. Optical imaging of electrical activity using genetically encoded voltage indicators (GEVIs) has the potential to meet this challenge. Currently prevalent GEVIs are based on the voltage-sensitive fluorescent protein (VSFP) prototypical design or on the voltage dependent state transitions of microbial opsins. We recently introduced a new VSFP design in which the voltage-sensing domain (VSD) is sandwiched between a FRET pair of fluorescent proteins (termed VSFP-Butterflies) and also demonstrated a series of chimeric VSD in which portions of the VSD of Ciona intestinalis voltage-sensitive phosphatase (Ci-VSP) are substituted by homologous portions of a voltage-gated potassium channel subunit. These chimeric VSD had faster sensing kinetics than that of the native Ci-VSD. Here, we describe a new set of VSFPs that combine chimeric VSD with the Butterfly structure. We show that these chimeric VSFP-Butterflies can report membrane voltage oscillations of up to 200 Hz in cultured cells and report sensory evoked cortical population responses in living mice. This class of GEVIs may be suitable for imaging of brain rhythms in behaving mammalians.